Impacts of continuing education for health professionals in primary health care: A scoping review - Laianny Krizia Maia Pereira; José Adailton da Silva; Eva Emanuela L. Cavalcante Feitosa; Alexandre R. Caitano; Janaína Luana R. da Silva Valentim; Manoel Honorio Romão; Natalia Araújo do N. Batista; Lyane Ramalho Cortez; Karilany Dantas Coutinho; Aline de Pinho Dias; Thaísa G. F. M. S. Lima; Ricardo A. de M. Valentim; et al. (PLoS ONE, 2025)
Introduction Continuing Health Education (CHE) is an essential strategy for the continuous qualification of Primary Health Care (PHC) professionals, promoting knowledge updating and improving the quality of services. In Brazil, this process is especially relevant given the challenges faced by the Unified Health System (SUS) and the need for training aligned with local demands. Understanding the impact of CHE actions in PHC is crucial to identify their effects on professional practice and health outcomes. Objective To identify and analyze the evidence on the impacts of CHE for health professionals in the context of Primary Health Care in Brazil. Method This is a scoping review conducted according to the Joanna Briggs Institute (JBI) guidelines and reported based on the PRISMA-ScR checklist. The search was performed in MEDLINE/PubMed, SciELO, LILACS, EMBASE, and Web of Science, and in gray literature through Google Scholar. Studies were selected independently by two researchers using Rayyan software. Results A total of 16 studies were included, of which 15 were scientific articles and one a doctoral thesis. Most of the CHE actions analyzed were carried out in person (56%), although technology-mediated online teaching and hybrid approaches have intensified in recent years. The studies covered a range of thematic areas, including family health, the prevention of sexually transmitted infections, child development, and the use of herbal medicines. The evaluation of the impact of CHE focused primarily on work process indicators – such as adherence to protocols, teamwork, and changes in professional practice – while health outcome indicators, such as improved prenatal care, vaccination coverage, and control of chronic diseases, were less frequently analyzed. Conclusion Continuing health education has a positive impact on the training of primary care professionals and the qualification of health services. However, measuring the effects of continuing education on health outcomes remains incipient, pointing to the need for more robust studies that assess long-term impacts. In addition, the expansion of flexible strategies, such as technology-mediated teaching and hybrid approaches, can contribute to greater equity in access to professional training, aligning with the Sustainable Development Goals (SDGs) and strengthening primary care in Brazil. Pre-registration